Exploring wage workers’ leisure travel: The role of structural constraints on the extensive and intensive margins of travel - Shin, Seonho (Tourism Economics, 2025)
For wage workers, travel is facilitated by stable, predictable incomes but hindered by rigid time limitations. Despite these particular circumstances, no empirical study has yet examined how the two most important structural constraints—time and money—relate to the extensive and intensive margins of their leisure travel. The present study explores this issue using population-representative, government-collected, high-dimensional micro-level data from South Korea with N ≈ 88, 000 over multiple years. Estimates from the zero-inflated negative binomial model suggest that (i) for overseas travel, while the extensive margin is influenced by both time and money factors, the intensive margin depends solely on the money factor, but (ii) for domestic travel, both margins are affected by both factors. An extended model demonstrates that time and money interplay in wage workers’ leisure travel; one factor tends to play a meaningful role when accompanied by adequate levels of the other factor, highlighting that both must function in tandem.
Keywords: leisure travel; money; time; wage workers; zero-inflated negative binomial model